PRODUCTION OF NARRATIVES AT WORK IN THE ICU NEONATAL AND PEDIATRIC - Butinholli Rangel, Camila (LINKSCIENCEPLACE, 2026)
This is a qualitative research based on narrative stories produced by means of inquiry, workshop and by the researcher`s experience. For the purposes of the present work, some accounts were inspired on self-etnnography. The health professionals from seven specialties, that work in the neonatal and pediatric ICU2 on the Public Hospital in the Rio de Janeiro State countryside , deals with of birth, pain and death of children.The research shows how they identify the signs of suffering at work. We believe that the use of narratives is a device capable of including those dimensions of experience from which one tries to distance oneself (Bruner,1991), thus producing knowledge about the life and the death in the work process developed.